Restorasi Cekat Sementara yang Diperkuat untuk Pemakaian Jangka Panjang - Riemawati A. Lesmana (Faculty of Dentistry, Universitas Indonesia, 2015)
Fixed provisional restorations are absolutely required in the treatment with crowns and fixed partial dentures, to protect the dental pulp that becomes sensitive after preparation, and also periodontal tissues. There are many other advantages, for example stabilizing the occlusion in the treatment of temporo mandibular joint and to prevent tooth movement in the treatment of periodontal diseases (splinting). For the last two purposes, fabrications of long term fixed provisional restorations are required. In this article we describe the conditions of a provisional restorations based on a diagnostic wax-up.